Parental control for mobile application - Cheong, Yong Jian (2014)
Nowadays, it is not weird that almost everyone have a mobile device. This statement also refer to the children nowadays. Children can be easily access internet just with a few touch of finger. This action may bring to unsafe exposure to our children. They would learn something bad from internet. Sometimes, parents are busying for life, they may not care about their children. Even though like this, they still worrying about their children. But too much care may lead to rebel of children. To prevent it from happening, a control application on mobile device will be very handful to every parents. Simple Launcher serves as a controlling app to ease the parents in monitoring their children' activities without interfering them and to check the record of their children when and where their children spent on past time. The methodology used in this project is Software Development Life Cycle (SDLC). Basically, Simple Launcher has PIN lock function that lock the app from the children. It can also filter the application which parents can select certain application installed to be allowed to their children to use. Furthermore, parents can use Simple Launcher to check the call log and message log to track their children' activities.